RANCANGAN APLIKASI PENCARIAN FILE PADA DIRECTORI WINDOWS DENGAN MENGGUNAKAN METODE BREADTH FIRST SEARCH - Sitompul, Krisman; Harianja, Andy Paul (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2021)
The current technological developments with the facilities provided are sufficient to motivate many parties to be able to find and obtain the maximum possible information, even as short as possible. This is what makes computer users to search or search the data / documents needed by using search engine facilities. However, very often the search results are unrelated, making it difficult to find the information needed. Searching is a process that is often used in data management. The search process is to find a certain value (data) in a set of data of the same type (either the base type or the form type). Data can be stored temporarily in main memory or stored permanently in secondary memory (tape or disk). In main memory, the common data storage structure is in the form of an array or table (array), while in secondary memory it is an archive (file). The search algorithm that will be discussed starts with one of the search algorithms that can be applied in a search in a directory, namely Breadth First Search (BFS).